Diversity of large mammals in the Marañón–Huallaga landscape, Peru: with notes on rare species. Issue 4 (2nd October 2018) - Shanee, Sam; Shanee, Noga
ABSTRACT: Peru is one of the most biodiverse countries on earth. Its northern montane forests are home to levels of biodiversity similar to those in the much larger Amazonian lowlands. We carried out rapid surveys of large mammal presence at 9 sites between the Marañón and Huallaga river valleys in Amazonas and San Martin, Peru. We calculated alpha and beta diversity for all sites and tested the effect of different habitat types, size of survey area and altitudinal range on diversity levels among sites. We recorded the presence of 57 large mammal species representing 45 genera, 29 families and 10 orders. There were significant differences in the number of species recorded among sites, ecoregions and vegetation types. Positive correlations were found between alpha diversity and the size and altitudinal range of an area. We found a weak correlation between indices of beta diversity in different vegetation types with altitudinal range. Additionally, we present range extensions for several species.